Dampak Penyusutan Air Tanah Di Kelurahan Bandarharjo Pesisir Kota Semarang - Ariska Ardi Lutfi; Kasanah kasanah; Nuryani Nuryani (Indonesian Journal of Geography Education, 2021)
Water is the most important thing for our well-being. In human life water is used for drinking, food processing, bath, energy, transport, agriculture, industry, and recreation. Communities in the Lower Semarang area mostly depend on the PDAM Tirta Moedal owned by the BUMD of the City of Semarang regarding water resources, although a small portion of the community uses dug wells or bucket wells as well as bore wells. The purpose of this study is: (1) To determine the factors that affect the shrinkage of the ground water in the coastal areas of semarang. (2) To determine the impact that occurs from the shrinkage of the ground water on the coast of semarang. (3) To know how to cope with the shrinkage of the ground water in the coastal areas of semarang. This research is a descriptive qualitative research. Data collection techniques done with interviews, observation, and documentation. Data obtained from interviews of entrepreneurs drill wells and local community leaders as well as the results of the observation. The data analysis, namely data reduction, data model/data presentation, and conclusion/verification conclusion. The results of the research of the impact of the depreciation of ground water in Depreciation in the Bandarharjo Urban Village of Semarang City are: (1) the Intrusion of sea water, due to the layout of the village close to the sea then the sea water intrusion is a thing that must happen if the water land continued to be exploited. (2) Flooding, in the coastal region of Semarang City is experiencing three types of flooding, namely flooding due to tidal or tide, the flood due to the large volume of rain water that fell, and floods from upstream areas. (3) the Surface of the soil decreases, the Semarang City especially the coastal region each year has decreased the surface of the soil about 10 cm annually. It is caused by a rise in the volume of sea water due to global warming and the impact of the drilling of ground water on a large scale. (4) Damage to infrastructure, due to the often overwritten flood then eventually the infrastructure will be damaged. Especially if often exposed to salty sea water, this can make the infrastructure becomes more rapid rusting (corrosion). (5) it is Difficult to find a source of clean water, if the water supply has been exhausted, then the community will be confusion to meet the needs of day-to-day, because the sea water can not meet the needs of day-to-day.